Oxidative Stress Markers in Sputum. (14th January 2016) - Antus, Balazs
Abstract : Although oxidative stress is thought to play a pivotal role in the pathogenesis of inflammatory airway diseases, its assessment in clinical practice remains elusive. In recent years, it has been conceptualized that oxidative stress markers in sputum should be employed to monitor oxidative processes in patients with asthma, chronic obstructive pulmonary disease (COPD), or cystic fibrosis (CF). In this review, the use of sputum-based oxidative markers was explored and potential clinical applications were considered. Among lipid peroxidation-derived products, 8-isoprostane and malondialdehyde have been the most frequently investigated, while nitrosothiols and nitrotyrosine may serve as markers of nitrosative stress. Several studies have showed higher levels of these products in patients with asthma, COPD, or CF compared to healthy subjects. Marker concentrations could be further increased during exacerbations and decreased along with recovery of these diseases. Measurement of oxidized guanine species and antioxidant enzymes in the sputum could be other approaches for assessing oxidative stress in pulmonary patients. Collectively, even though there are promising findings in this field, further clinical studies using more established detection techniques are needed to clearly show the benefit of these measurements in the follow-up of patients with inflammatory airway diseases.